2019
DOI: 10.4067/s0717-95022019000200757
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Traits of the Heart in Standard and Mutational Colour Variants of American Mink ( Neovison vison )

Abstract: traits of the heart in standard and mutational colour variants of American mink (Neovison vison). Int. J. Morphol., 37(2):757-765, 2019. SUMMARY:The aim of this study was to estimate the values of morphological traits of myocardium in American minks. The study was conducted on 342 male mink hearts and 416 female mink hearts. Mink coat coloration resulting from mutation or crossbreeding of mutational variants with each other and sex were assumed as a source of variation. Carcass, lung and heart weights, heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Studies examining the impacts of domestication have typically focused on features such as bone shape [7], behaviour [8] and genetics [9]. Assessment of internal organs in domesticated taxa, including structural heart morphology, has received little attention (but see [10,11]). A higher proportion of studies investigating the impact of domestication on heart morphology have done so in fish [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the impacts of domestication have typically focused on features such as bone shape [7], behaviour [8] and genetics [9]. Assessment of internal organs in domesticated taxa, including structural heart morphology, has received little attention (but see [10,11]). A higher proportion of studies investigating the impact of domestication on heart morphology have done so in fish [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Not only do the resulting mink varieties differ in the color of the coat and breeding performance, but also in the average body weight and other traits. For example, it has been found that the minks of different color varieties may exhibit different morphological features of the skull [Baranowski et al 2014], may differ in the size of the heart or in the structure and shape of the coronary vessels Żuk 2019, Baranowski andŻuk 2020]. The apparent significant inequalities in the body weight of the mink of different colors result from genetics rather than from the environment, as housing and feeding conditions of the farm are the same [Liu et al 2011, Do andMiar 2020].…”
Section: Introductionmentioning
confidence: 99%